Pengaruh Budaya Pesan Antar Makanan terhadap Niat Perilaku Konsumen pada Masa Pandemic Covid-19 di Indonesia - Triana Faizal Rachman; Kurniawati Kurniawati (Universitas Batanghari, 2022)
The purpose of this study is understanding consumer behavior in using Online Food Delivery (OFD) service, considering the lockdown policy that is implemented in several countries have changed consumer behavior. Using the Goal-Directed Behavior (MGB) model, this study investigates what consumers feel while using OFD services. The method used is collecting responses from online food delivery service users throughout May 2022. A total of 271 responses were collected and then analyzed using AMOS. Measurements and structural models are evaluated to ensure that the Structural Equation Modeling (SEM) is valid. The results show that only Positive Anticipated Emotion (PAE) and Perceived Behavioral Control (PBC) are significantly affecting behavioral intention which is mediated by desire. It also shows that desire is significantly affecting behavioral intention. The results of this study provides information for OFD service providers and experts about what is forcing the urbanites into using OFD services in the midst of a pandemic. It also enables OFD companies to realign their operations to address issues and changes in consumer behavior. The managerial implications of this research provide insights for OFD providers to develop new strategies and approaches on business development and consumer retention post-pandemic